Concept maps and the meaningful learning of science - José Antonio C. S. Valadares (Universidad de Granada, 2013)
The foundations of the Meaningful Learning Theory (MLT) were laid by David Ausubel. The MLT was highly valued by the contributions of Joseph Novak and D. B. Gowin. Unlike other learning theories, the MLT has an operational component, since there are some instruments based on it and with the meaningful learning facilitation as aim. These tools were designated graphic organizers by John Trowbridge and James Wandersee (2000, pp. 100-129). One of them is the concept map created by Novak to extract meanings from an amalgam of information, having currently many applications. The other one is the Vee diagram or knowledge Vee, also called epistemological Vee or heuristic Vee. It was created by Gowin, and is an excellent organizer, for example to unpack and make transparent the unclear information from an information source. Both instruments help us in processing and becoming conceptually transparent the information, to facilitate the cognitive process of new meanings construction. In this work, after a brief introduction, it will be developed the epistemological and psychological grounds of MLT, followed by a reference to constructivist learning environments facilitators of the meaningful learning, the characterization of concept maps and exemplification of its use in various applications that have proved to be very effective from the standpoint of meaningful learning.